PENGARUH FREE CASH FLOW, KEBIJAKAN DIVIDEN, DAN ESG TERHADAP RETURN SAHAM - Rafiqi, Muhamad Hasbi; Zenabia, Tsarina (Jurnal Riset Terapan Akuntansi, 2025)
The purpose of this study is to empirically prove the effect Free Cash Flow, Dividend Policy, and ESG on Stock Return. This is a quantitative study with a population consisting of all companies on the IDX LQ45 index for the period 2019-2023. Sampling was conducted using a nonprobability sampling approach with purposive sampling. The data was processed using E-views. The results of this study show that simultaneously, free cash flow, dividend policy, and ESG have a significant positive effect on stock returns. Partially, free cash flow has a significant positive effect on stock returns, while dividend policy and ESG do not have a significant effect on stock returns. Keywords: Free Cash Flow, Dividend Policy, ESG, Stock Return